2001
DOI: 10.1177/107319110100800101
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of African American and White American Veteran MMPI-2 Profiles

Abstract: The present study compared a matched sample of 180 African American and 180 White American veterans who completed the MMPI-2 as a part of their evaluation while receiving inpatient psychiatric treatment. Findings indicated no significant multivariate or univariate effects associated with race on the basic validity and clinical scales, a significant multivariate effect but no significant univariate effects associated with race across the supplementary scales. Overall the two groups had very similar mean profile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 5 publications
1
2
0
Order By: Relevance
“…Although the results of this analysis suggest that this potentially confounding variable was not influential in the current results, further evaluation of the effects of ethnicity is indicated in future research. Our findings regarding ethnicity are similar to the results obtained by Munley, Murray, Morris, and Baines (2001), who found that few differences on MMPI-2 scales could be associated with ethnicity once participants were matched on diagnosis.…”
Section: Discussionsupporting
confidence: 90%
“…Although the results of this analysis suggest that this potentially confounding variable was not influential in the current results, further evaluation of the effects of ethnicity is indicated in future research. Our findings regarding ethnicity are similar to the results obtained by Munley, Murray, Morris, and Baines (2001), who found that few differences on MMPI-2 scales could be associated with ethnicity once participants were matched on diagnosis.…”
Section: Discussionsupporting
confidence: 90%
“…The two groups did not differ significantly on age or education; however, the African American group was less likely to have been married. As was the case for the original MMPI, in ethnic groups matched closely on demographic variables, previously observed mean differences on scale scores on the MMPI-2 tend to diminish or disappear (Greene, 1987; Munley, Morris, Murray, & Baines, 2001).…”
mentioning
confidence: 61%
“…Some researchers suggest differences that emerge may be because of education and socioeconomic status (Greene, 1987; Gynther, 1972). Although some studies have adjusted for age (Davis & Greenblatt, 1990; Davis et al, 1990; Munley, Morris, Murray, & Baines, 2001), no studies to date have adjusted for other potential confounding variables such as education and socioeconomic status. To date, no compelling explanation of these group differences has emerged.…”
mentioning
confidence: 99%